A competitive ELISA for quantifying serum CD147: Reduction of soluble cd147 levels in cancer patient sera - Moonsom S. (2014)
CD147/EMMPRIN (extracellular matrix metalloproteinase inducer) is a cell surface glycoprotein that displays increased expression in many cancers. It has been previously demonstrated to participate in cancer metastasis and progression. In this study we used an anti-CD147 monoclonal antibody and a recombinant CD147 protein generated in our laboratory to establish a competitive ELISA for quantifying serum CD147 levels. Unexpectedly, the CD147 level was highest in sera of normal subjects and significantly reduced in sera of cancer patients. There was no significant difference in serum CD147 level between benign, non-metastatic, and metastatic stages of cancers. In regard to liver diseases, the maximal CD147 level was observed in sera of patients with hepatitis and hepatocellular carcinoma, and significantly decreased in patients with liver cirrhosis and cholangiocarcinoma. Our results imply that there may be homeostasis of CD147 levels in sera under normal physiological conditions, while such a level is altered in cancer patients. © 2010, Mary Ann Liebert, Inc.